1993
DOI: 10.1002/aic.690390814
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of scrap tires and conversion of chars to activated carbon

Abstract: The primary objective of this work was to demonstrate the conversion of scrap tires to activated carbon. We have been successful in this endeavor, producing carbons with surface areas greater than 500 m2/g and significant micropore volumes. Tire shreddings were pyrolyzed in batch reactors, and the pyrolysis chars activated by reaction with superheated steam. Solid products of pyrolysis and activation were studied with nitrogen adsorption techniques. We find that the porosity development during steam activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 25 publications
1
60
0
Order By: Relevance
“…Finally, it is seen that increasing the value of the carbon product from a conservative price of $200 per ton (10¢ per pound) to a more optimistic price of $500 per ton (25¢ per pound) increases the ROI by nearly 20%. In view of the research results discussed earlier, (69)(70)(71) carbon priced at $500 per ton does not seem unrealistic.…”
Section: Pyrolysismentioning
confidence: 82%
See 2 more Smart Citations
“…Finally, it is seen that increasing the value of the carbon product from a conservative price of $200 per ton (10¢ per pound) to a more optimistic price of $500 per ton (25¢ per pound) increases the ROI by nearly 20%. In view of the research results discussed earlier, (69)(70)(71) carbon priced at $500 per ton does not seem unrealistic.…”
Section: Pyrolysismentioning
confidence: 82%
“…Merchant and Petrich (69) produced carbons with surface areas greater than 500 m 2 /g by steam activation of tire pyrolysis char. They observe porosity development similar to that found for various other chars.…”
Section: Coprocessing Of Plastics With Coalmentioning
confidence: 99%
See 1 more Smart Citation
“…Small amounts of zinc oxide and stearic acid were added to control the vulcanization process and to enhance the properties of the final products. 24 Electron microscopy with elemental X-ray analysis showed that the positions of zinc deposits within tire char particles coincide with the positions of sulfur deposits, suggesting that ZnO and sulfur in the tires can react with each other to form ZnS during the pyrolysis. 25 This study found that, after pyrolysis at 420°C, ZnS (58.9 wt%) was still retained on the surface of carbon black derived from the pyrolysis of waste tires.…”
Section: Fitting Of the Oxygen Esca Spectramentioning
confidence: 99%
“…Vijaya Ku mar et al [18] had investigated the performance and emission characteristics of diesel engine with three hole injector by using tyre oil blends and their results shows that 20% tyre oil blend was given better performance compared with diesel and other blends at all injections pressures. [19][20][21][22] are conducted experiments on diesel engine fuelled with tyre pyrolysis oil blended at different proportions to evaluate the performance and emissions with and without ethanol. [23,24] are investigated the performance, emission and combustion studies using distilled tyre pyrolysis oil blends on diesel engine without any engine modificat ion.…”
Section: Introductionmentioning
confidence: 99%